Deveres e responsabilidade dos administradores da S/A - Oliveira, Daniele de Lima de (2008)
The corporations have the big challenge to overcome the competitiveness of the market and to be subject to the restructuring process of the corporate organization. The range of this restructuring process directly reflects on the management of the company, which has the main objective of achieving profits, observing institutional, legal and social rules in order to demonstrate its real effectiveness. This dissertation has the objective of pointing out the most important aspects of the duties and responsibilities of the managers in charge of this challenge. This dissertation first presents the historical evolution of the corporations, as much in Europe as in Brazil, followed by the study of the social bodies, specially the Board of Directors and Management Board to demonstrate the Administrative System of the corporations. Afterwards, this dissertation points out the duties of the administrators focused on diligence, ethics, exercise of power, loyalty and information duty. The responsibility of the managers in civil sphere is foreseen, including the ultra vires acts, the issue regarding the joint liability among their members and the social and individual acts which they are subject to, considering that they may use the good faith principles as an exclusion of responsibility. It also has a brief explanation regarding the responsibility of the manager in the administrative sphere of the Stock Exchange Commission (CVM) and his responsibility concerning tax aspects. This theme was chosen due to the importance of the honest, ethic and moral conduct of the managers before the company and the society. The purpose of this dissertation is to expose the true quality of the manager of a company in regard to the compliance of the legal and institutional rules in order to achieve the main social objective in benefit of the ones that integrate the company, as much as internally as externally